COMPOSITION AND AGE OF THE DAOHUGOU HYMENOPTERAN (INSECTA, HYMENOPTERA = VESPIDA) ASSEMBLAGE FROM INNER MONGOLIA, CHINA - Rasnitsyn A.P.; Zhang H. (My University, 2004)
Hymenopteran fossils from Daohugou, Inner Mongolia, China are assigned to 17 families. These include, in decreasing order of importance, Ephialtitidae, Xyelidae, Siricidae, Xyelydidae, Anaxyelidae, Karatavitidae s.l., Mesoserphidae, Megalyridae and Praeaulacidae. Analysis of the taxonomic composition suggests that the assemblage is of Mid Jurassic age. The rather low abundance of Xyelidae suggests that the climate in Daohugou during the Mid Jurassic might have been thermally intermediate between that of peri-Baikal Siberia during the Early/Mid Jurassic transition and southern Kazakhstan during the early Late Jurassic. A new family, Protosiricidae fam. nov., is established herein and the family Gigasiricidae is reduced in rank to Gigasiricinae and referred to the Siricidae.
Keywords: Hymenoptera; Mesozoic::Jurassic; Мезозой::Юрская